Pelatihan Manajemen Media Sosial untuk Membangun Personal Branding Siswa SMK Negeri 1 Dendang - Ayu Gede Willdahlia; I Dewa Gede Aristana; I Dewa Putu Gede Wiyata; Ni Kade Ayu Nirwana; Ni Made Sudianti; I Kadek Krisna Dwipayana Putra; I Gusti Ngurah Agung Prama Daniswara Puta Kusuma (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Social Media Management Training to Improve Student Branding at SMK Negeri 1 Dendang aims to equip students with the skills and knowledge necessary to build a strong personal brand through social media platforms. In today's digital era, effective use of social media is essential not only for communication but also for career development, entrepreneurship, and professional networking. This initiative was born from the observed need to improve students' digital presence, self-promotion abilities, and readiness to face the competitive job market, especially since many vocational students are highly skilled in their technical domains but lack the ability to present themselves effectively in the digital space. The implementation process includes a series of workshops, hands-on content creation activities, peer reviews, and mentorship sessions. Students are taught to manage their personal profiles, curate content that aligns with their career goals, and analyze engagement metrics to refine their approach. Teachers are also involved to ensure continued guidance after the program concludes. The outcomes of this program include increased student awareness of personal branding, improved digital communication skills, and greater confidence in leveraging social media as a professional tool. Furthermore, the initiative contributes to the school's broader objective of preparing graduates who are not only technically competent but also digitally savvy and market-ready.